Epidemiologic study of chronic osteomyelitis in Paktya and Kabul, Afghanistan - Walikhan, Oryakhil; Bismellah, Nejrabi (International Journal of Research in Medical Sciences, 2020)
Background: Osteomyelitis is an infection of the bone that can occur from direct or indirect invasion by a pathogens, both of these types can potentially progress to subacute and chronic osteomyelitis that lasts longer than 4 weeks. This disease has important characteristics such as long-term clinical course, long periods of silence, the treatment of the recurrence of serious complications of the disease is difficult financially and it takes a lot of money epidemiology of chronic osteomyelitis in the Afghanistan is largely unknown. The aim of this study was epidemiologic study of chronic osteomyelitis in adult clients of Paktya city regional hospital and Wazir Akbar Khan Hospital in Kabul city of Afghanistan. Methods: This descriptive cross-sectional study was performed in patients’ with chronic osteomyelitis who referred in this two hospitals in Paktya city regional hospital and the Wazir Akbar Khan hospital in Kabul During the March 2019 to March 2020, 70 patients were identified with chronic osteomyelitis. The information required for the study, such as general information, underlying diseases of the patients collected from these two medical centers. After encoding, the necessary information was entered into the computer and analyzed. Results: According to the findings of this study the prevalence of chronic bone infections in male were 64% (n=45) in female were 36% (n=25), current findings showed 44.3% of all patient involved with tibial (n=31) chronic osteomyelitis and the most common underlying disease causing chronic osteomyelitis is the direct entry of infection as a result of trauma. Conclusions: Our study showed the chronic osteomyelitis is higher in the male population than in the female population and highest incidence of chronic osteomyelitis site was tibia result of trauma because of humid climate, poor personal and hospital environmental health status and relatively poor medical facilities in Afghanistan may contribute to higher morbidity.